Context effects in lexical access: a meta-analysis. - Lucas, Margery (Memory & Cognition, 1999)
The modularity hypothesis was evaluated in this review of 25 studies that investigated context effects in early lexical processing. Selection criteria restricted the review to priming studies and to studies that presented the target word before or at the end of the prime word. Meta-analysis was used to provide summary information about the 17 studies in the review for which effect sizes could be calculated. Overall, the analysis revealed a small effect of context on lexical access. Results provide a disconfirmation of the modularity hypothesis; although multiple interpretations of a word were sometimes accessed, the contextually appropriate interpretation was consistently more strongly activated. The lack of significant heterogeneity of variance suggests that the variability observed across studies was due to sampling error; however, task, timing of target presentation, meaning frequency, type of target, and type of context were identified as potential moderator variables. Reprinted by permission of the publisher.